Accreditation of medical schools: the question of purpose and outcomes - Mohd Adnan, Nor Azila; Tan, C.P.L. (Malaysian Medical Association, 2005)
Accreditation is a process by which official accrediting bodies evaluate institutions using a set of criteria and standards, following established procedures, to ensure a high quality of education needed to produce highly competent graduates. Additional objectives include (1) ensuring quality institutional functioning, (2) strengthening capabilities of educational institutions for service to the nation and (3) improving public confidence in medical schools. The accreditation process provides an opportunity for the institution to critically reflect upon all the aspects of its programme and the level of compliance or attainment of the requirements. The self-evaluation exercise, which identifies strengths and weaknesses, is perceived as formative. It is envisaged that eventually institutions will adopt a learning culture for curriculum development, implementation, monitoring and matching the outcomes. In conclusion, periodic accreditation activities can act as a "monitoring" system to ensure that the quality of medical education is maintained according to established standards.